Counselling psychology in the United Kingdom. Issue 2 (2nd April 2016) - Jones Nielsen, Jessica D.; Nicholas, Helen
Abstract : Counselling psychology within the UK has grown over the last three decades, adapting to many changes in the field of applied psychology, whilst remaining true to its core values and humanistic origins. The identity of counselling psychology is strongly rooted in a relational stance and applied psychology, where attention to psychological formulation is given to improve psychological functioning and well-being. This article outlines a brief history of counselling psychology in the UK, the training process, credentialing and looks at some important challenges and future directions for counselling psychology in the UK. A proportion of the members from the British Psychological Society's division of counselling psychology (DCoP, N = 148) took part in the study. Participants provided demographic, training, employment, workplace and career pathway information obtained through an online questionnaire distributed to all DCoP members. On the whole, DCoP members are working in a variety of areas within the UK and the findings of this article contribute to the international study comparing counselling psychology across the globe.